Correction to: Case report: acute clinical presentation and neonatal management of primary hyperparathyroidism due to a novel CaSR mutation - Manuela Capozza; Iolanda Chinellato; Vito Guarnieri; Natascia Di Iorgi; Maria Accadia; Cristina Traggiai; Girolamo Mattioli; Antonio Di Mauro; Nicola Laforgia (BMC, 2019)
In the published article [1], an error has been noticed in the author group section.